ANALISIS EFEKTIVITAS DAN EFISIENSI KINERJA KEUANGAN ORGANISASI PENGELOLA ZAKAT DENGAN METODE ALLOCATION TO COLLECTION RATIO (ACR) DAN DATA ENVELOPMENT ANALYSIS (DEA) (Studi Kasus di Kabupaten Banyumas Tahun 2021–2025) - Zakia Aminia Gustiana; Abdul Rohman (Diponegoro Journal of Accounting, 2026)
The effective and efficient management of Zakat, Infaq, and Sadaqah (ZIS) funds is an important aspect in supporting the optimization of the role of Zakat Management Organizations (OPZ) in improving social welfare. Banyumas Regency has considerable potential for ZIS fund collection due to the predominance of its Muslim population. However, a gap still exists between the potential and the actual realization of ZIS fund collection, making it necessary to evaluate the performance of OPZ. This study aims to analyze the effectiveness and efficiency of the financial performance of OPZ in Banyumas Regency during the 2021–2025 period. The research objects consist of BAZNAS Banyumas Regency, LAZISMU Banyumas Regency, and LAZISNU Banyumas Regency.This study employs a quantitative approach using secondary data obtained from the financial statements of each OPZ. Effectiveness was measured using the Allocation to Collection Ratio (ACR) method, which compares the amount of ZIS funds distributed to the amount collected. Meanwhile, efficiency was measured using the Data Envelopment Analysis (DEA) method with an output-oriented approach and the Variable Return to Scale (VRS) assumption.The results indicate that all OPZ in Banyumas Regency achieved a very high level of effectiveness and were classified as highly effective, indicating that the collected ZIS funds were distributed optimally to eligible beneficiaries. The efficiency analysis shows that LAZISMU Banyumas Regency consistently achieved an efficient condition throughout the study period, while BAZNAS Banyumas Regency and LAZISNU Banyumas Regency experienced inefficiencies in several periods due to suboptimal input utilization and less-than-optimal output achievement. Overall, the management of ZIS funds by OPZ in Banyumas Regency has been highly effective and reasonably efficient, although optimal efficiency has not been consistently maintained by all organizations. This study is expected to serve as an evaluation tool for OPZ in improving the quality of sustainable ZIS fund management.